Language Training as a Driver of Community Empowerment and Sustainable Heritage Tourism: A Case Study from the Yogyakarta Royal Palace - Yeni Artanti; Sudarmaji Sudarmaji; Andy Bayu Nugroho; Jihan Afifah Syafitri; Heri Septian Munggaran; Irham Ramadhan (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Cultural heritage tourism increasingly requires skilled human mediation to ensure meaningful intercultural exchange and sustainable development. However, many heritage tour guides, particularly those operating within traditional cultural institutions, face limitations in foreign language competence that hinder effective communication with international visitors. Responding to this challenge, this study investigates a foreign language training program implemented for tour guides at Kawedhanan Hageng Panitrapura, Karaton Ngayogyakarta Hadiningrat, Indonesia, and examines its role in community empowerment and local realization of the Sustainable Development Goals. The study aims to analyze how contextually grounded multilingual training contributes to guides’ communicative competence, professional confidence, and cultural representation. A qualitative case study design was employed, drawing on data from post training questionnaires, non-participant observations, and participant reflective feedback involving 22 active heritage tour guides. Data were analyzed thematically using an interpretive framework informed by communicative competence theory, empowerment theory, and education for sustainable development. The findings reveal that the training enhanced participants’ basic communicative abilities in English, French, and German, increased their confidence in interacting with foreign visitors, and strengthened their perception of multilingualism as cultural and professional capital. Contextual and communicative learning activities were identified as particularly effective, while online delivery-imposed constraints on oral interaction and sustained engagement. Beyond linguistic outcomes, the program fostered a stronger sense of professional identity and cultural responsibility among participants. The study concludes that foreign language training embedded within a traditional royal institution can function as a meaningful empowerment mechanism and contribute to multiple Sustainable Development Goals. It highlights the importance of culturally grounded, institutionally legitimate, and partnership-based approaches to language education in heritage tourism contexts.